Hubungan Try Out dengan Tingkat Kelulusan Uji Kompetensi Perawat di Universitas Sembilanbelas November Kolaka - Heriviyatno Julika Siagian; Arman Sagita (Jurnal Surya Medika (JSM), 2019)
Competency Test is a process of measuring students’ knowledge, skills, and attitude in universities that organize higher education in Health. Data obtained from the results of the nurse competency test at Sembilanbelas November University in Kolaka from July 2017 period IX showed that 2 of 18 (11%) registered participants passed the test and 16 others (89%) did not pass it. The purpose of this study was to determine the factors correlated to the graduation level of the competency test at Sembilanbelas November University in Kolaka. This type of research was Analytic using the design of Cross-Sectional Study. The population of this study was 80 people where 67 of them were taken as sample using the Simple Random Sampling technique which was then analyzed using Spearman-Rank test method. The results of Statistical tests showed that there is a correlation between the try out variable and the graduation of competency test (P-value = 0.013 and correlation coefficient = 0.301), there is no correlation between Grade Point Average variable and the graduation of competency test (P-value = 0.349 and correlation coefficient = 0.116), and there is a correlation between learning style variable and the graduation of competency test (P-value = 0,000 and correlation coefficient = 0.517). It is expected that nursing colleges pay more attention to factors that have a close correlation with the graduation level of nursing competency test. One of them is by increasing the number of try out for students and making student learning styles effective in order to improve the graduation level of the nurse competency test.